2018
DOI: 10.1177/0363546518755717
|View full text |Cite
|
Sign up to set email alerts
|

Does Capsular Laxity Lead to Microinstability of the Native Hip?

Abstract: Capsular laxity alters normal kinematics (joint rotation and femoral head translation) of the hip, potentially leading to abnormal femoral-acetabular contact and joint degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…Microinstability has been classified based on bony or soft tissue origin, with 2 of the most common causes being acetabular undercoverage and ligamentous laxity. 10,14 Signs of microinstability on physical examination were extremely prevalent in this (11/14), and 81.8% of patients (9/11) presented with a Beighton score of 4 or higher. A recent study reported a Beighton score of 4 or higher in only 18.9% of patients undergoing hip arthroscopy, significantly less common than the demonstrated rate in the current study.…”
Section: Discussionmentioning
confidence: 86%
“…Microinstability has been classified based on bony or soft tissue origin, with 2 of the most common causes being acetabular undercoverage and ligamentous laxity. 10,14 Signs of microinstability on physical examination were extremely prevalent in this (11/14), and 81.8% of patients (9/11) presented with a Beighton score of 4 or higher. A recent study reported a Beighton score of 4 or higher in only 18.9% of patients undergoing hip arthroscopy, significantly less common than the demonstrated rate in the current study.…”
Section: Discussionmentioning
confidence: 86%
“…The positional relationship between the femoral head and the acetabulum with hip neutral position was reported as not different between supine AP pelvic radiographs and weight-bearing conditions [32]. Additionally, this positional relationship is concentric within 30˚of flexion in the normal hip [33]. Nevertheless, we have made effort to obtain the hip neutral position CT images.…”
Section: Plos Onementioning
confidence: 96%
“…Earlier studies explored the biomechanical contributions of local hip anatomy to stability, 4,5 and this evolved into a greater understanding of how the capsule itself taken together with pericapsular structures contributes to hip stability. 3,[6][7][8] More recently, the debate over the importance of capsular repair 9,10 and various repair strategies [11][12][13] has culminated with several outcome studies that leave no question as to the evidence in support of superior surgical outcomes with capsular repair. 14,15 Yes, folks, it is quite clear that the capsule must be addressed during routine arthroscopy.…”
Section: See Related Article On Page 116mentioning
confidence: 99%